Description of Biomaibacter acetigenes gen. nov., sp. nov., and proposal of Thermosediminibacterales ord. nov. containing two novel families of Tepidanaerobacteraceae fam. nov. and Thermosediminibacteraceae fam. nov. Issue 12 (12th September 2019) - Zhang, Xue; Tu, Bo; Lv, Xiao-meng; Lawson, Paul A.; Yang, Min; Dai, Li-rong; Zhang, Hui; Tang, Yue-Qin; Deng, Yu; Cheng, Lei
Abstract : A Gram-stain-negative, rod-shaped, chemoorganotrophic and anaerobic bacterium, strain SK-G1 T, was isolated from oily sludge sampled at the Shengli oilfield in PR China. Growth occurred with 0–30 g l −1 NaCl, at 40–65 °C and at pH 6.0–8.5. The predominant fatty acids were C14 : 0 and C13 : 0, and the major cellular polar lipids were phosphatidylglycerol and phosphatidylethanolamine. No respiratory quinone was detected. The genomic G+C content was 43.9 mol%. The strain had highest 16S rRNA gene sequence similarity (93.2 % identity) to Tepidanaerobacter syntrophicus DSM 15584 T . The phylogenetic, phenotypic and chemotaxonomic data showed that strain SK-G1 T (=CCAM 530 T =KCTC 15783 T =JCM 33158 T ) represents a novel species of a new genus Biomaibacteracetigenes gen. nov., sp. nov. The results of phylogenetic and phylogenomic analyses indicated that the genera Biomaibacter, Caldanaerovirga, Fervidicola, Tepidanaerobacter, Thermosediminibacter, Thermovenabulum and Thermovorax formed a clade with high bootstrap support distinguishing to other taxon within the order Thermoanaerobacterales . This clade is proposed as Thermosediminibacterales ord. nov. and includes Tepidanaerobacteraceae fam. nov. and Thermosediminibacteraceae fam. nov. Emended descriptions of the order Thermoanaerobacterales and family Syntrophomonadaceae are also provided.